A worldwide consensus on nudging? Not quite, but almost. Issue 1 (26th July 2017) - Sunstein, Cass R.; Reisch, Lucia A.; Rauber, Julius
Abstract: Nudges are choice‐preserving interventions that steer people's behavior in specific directions while still allowing them to go their own way. Some nudges have been controversial, because they are seen as objectionably paternalistic. This study reports on nationally representative surveys in eight diverse countries, investigating what people actually think about nudges and nudging. The study covers Australia, Brazil, Canada, China, Japan, Russia, South Africa, and South Korea. Generally, we find strong majority support for nudges in all countries, with the important exception of Japan, and with spectacularly high approval rates in China and South Korea. We connect the findings here to earlier studies involving Denmark, France, Germany, Hungary, Italy, the United Kingdom, and the United States. Our primary conclusion is that while citizens generally approve of health and safety nudges, the nations of the world appear to fall into three distinct categories: (i) a group of nations, mostly liberal democracies, where strong majorities approve of nudges whenever they (a) are seen to fit with the interests and values of most citizens and (b) do not have illicit purposes; (ii) a group of nations where overwhelming majorities approve of nearly all nudges; and (iii) a group of nations that usually show majority approval, but markedly reduced approval rates. We offer some speculations about the relationship between approval rates and trust.